2018
DOI: 10.1038/s41598-018-20566-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of anti-CD154 antibody in cynomolgus monkeys with advanced rheumatoid arthritis

Abstract: Rheumatoid arthritis is one major chronic inflammatory systemic autoimmune disease. The CD154-CD40 interactions play a critical role in the regulation of immune responses and the maintenance of autoimmunity. Therefore, we aimed to determine whether anti-CD154 antibody treatment show positive effects on immunomodulation and clinical improvement of sustained severe rheumatoid arthritis in cynomolgus monkeys. Arthritis was induced using chicken type II collagen (CII) and arthritic monkey were divided into control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…This suggests that the arthritis-resistant MHC allele may differ between species, even when they belong to the same genus. Previous studies have demonstrated CIA induction in M. fascicularis [6][7][8][9], however, there has been no evaluation of the genetic background of the Previous studies have demonstrated CIA induction in M. fascicularis, and have shown the therapeutic effects of IL-6 neutralizing agents in CIA [6,7,[16][17][18]. However, these studies did not use a standardized scoring system or conduct behavior and pain analysis, and did not evaluate bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the arthritis-resistant MHC allele may differ between species, even when they belong to the same genus. Previous studies have demonstrated CIA induction in M. fascicularis [6][7][8][9], however, there has been no evaluation of the genetic background of the Previous studies have demonstrated CIA induction in M. fascicularis, and have shown the therapeutic effects of IL-6 neutralizing agents in CIA [6,7,[16][17][18]. However, these studies did not use a standardized scoring system or conduct behavior and pain analysis, and did not evaluate bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…These CIA models, based on M. mulatta, had only a 70% induction rate for arthritis [4]. The cynomolgus monkey, M. fascicularis, has emerged as an alternative primate animal model for RA [6][7][8][9], however, a standardized scoring system has not yet been established for this model. Furthermore, osteoporosis is one of the major comorbidities of RA [10], and an evaluation of the degree of osteoporosis, such as bone density in primates models of RA, has not been conducted previously.…”
Section: Journal Of Translational Medicinementioning
confidence: 99%
“…This suggests that the arthritis-resistant MHC allele may differ between species, even when they belong to the same genus. Previous studies have demonstrated CIA induction in M. fascicularis [6][7][8][9], however, there has been no evaluation of the genetic background of the arthritis-resistant MHC allele. The present study showed that the speci c MHC alleles known to play crucial roles in the induction of CIA in M. mulatta were not active in M. fascicularis.…”
Section: Discussionmentioning
confidence: 99%
“…These CIA models, based on M. mulatta, had only a 70% induction rate for arthritis [4]. The cynomolgus monkey, M. fascicularis, has emerged as an alternative primate animal model for RA [6][7][8][9], however, a standardized scoring system…”
Section: Introductionmentioning
confidence: 99%
“…Both CD28-CD80/86 and CD154-CD40 interactions play an important role in B cell activation and proliferation, and CD154-CD40 ligation specifically provides key signaling for thymus-dependant humoral immunity responses, such as the isotype class-switching and affinity maturation required to generate high affinity anti-CII IgG autoantibodies [65][66][67]. Furthermore, previous research has demonstrated that the disruption of CD28-CD80/86 and CD154-CD40 interactions results in reduced anti-CII autoantibody titres, prevention of disease development, and/or amelioration of disease in CIA and other autoimmune arthritis models [68][69][70][71][72]. In other words, pro-inflammatory T cell development and activation is inhibited by BBR early, which leads to a later reduction in B cells reactive to CII stimulus, and this timing fits with classical T cell-mediated B cell activity.…”
Section: Discussionmentioning
confidence: 99%